PRE-STRUCTURED MODEL IN ERGONOMICS: APPLICATION IN A RURAL PROPERTY IN THE AMAZONIA : MODELO PRÉ-ESTRUTURADO EM ERGONOMIA: APLICAÇÃO EM UMA PROPRIEDADE RURAL NA AMAZÔNIA - Holanda Lopes, Rute; Castro do Nascimento, Joel; Taís Duarte, Eloá; Coelho, Moisés Andrade (Brazilian Journal of Production Engineering, 2020)
This study aims to apply Action Checkpoint for Agriculture on a rural property located in the municipality of Itacoatiara/Amazonas/Brazil.  Regarding the approach to the problem, this study is characterized as quali-quantitative and exploratory with regard to the objectives. Regarding the technical procedures for data collection, this is a case study. The research techniques used to operationalize the study were: indirect documentation (bibliographic research); intensive direct observation (in loco observation and interview); and extensive direct observation (form). Among the main results of the research stand out: identification of the main ergonomic aspects related to the studied property; the enterprise's need to adapt to regulatory standards and other ergonomic aspects; an indication of points for improving the productive environment; and building recommendations for future improvements. The relevance of the research resides in the application of the instrument (Action Checklist for Agriculture) essential to support rural properties in the identification of points for the improvement of the working environment in the traditional sector of the economy.